The Influence of Leadership and Work Discipline on Employee Performance at PT. XYZ Indonesia - Santika, Elsa; Hasanuddin Hasanuddin; Jumawan Jumawan; Fauzi, Achmad; Setyawati, Novita Wahyu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze whether the Influence of Leadership and Work Discipline on Employee Performance of PT. XYZ. The research method used in this study is a quantitative method. The sampling technique in this study used a saturated sample or census of 40 employees as respondents. The data collection technique used a questionnaire in several questions and was measured using a Likert Scale. Data analysis used the Structural Equation Modeling (SEM) method. Data was processed using SMART PLS 4.1 software. The results of the study showed that (X1) Leadership has a positive and significant effect on teacher performance. In addition, (X2) Work Discipline has a positive and significant effect on teacher performance.